Parallel Simulations of Manufacturing Processing using Simpy, a Python-Based Discrete Event Simulation Tool - Castillo, V. (Proceedings of the 2006 Winter Simulation Conference, 2006)
SimPy is a Python-based, interpreted simulation tool that offers the power and convenience of Python. It is able to launch processes and sub-processes using generators, which act autonomously and may interact using interrupts. SimPy offers other advantages over competing commercial codes in that it allows for modular development, use of a version control system such as CVS, can be made self-documenting with PyDoc, and is completely extensible. The convenience of an interpreted language, however, is offset for large models by slower than desired run times. This disadvantage can be compensated for by parallelizing the system using PyMPI, from the Eawrence Eivermore National Eaboratory. This work was performed under the auspices of the U.S. Department of Energy by University of California, Eawrence Livermore National Eaboratory under Contract W-7405-Eng-48